Persuasive Communication of Dangdut Tarling Pantura Singer To Attract Audience - Widia Ningsih (Politeknik Siber Cerdika Internasional, 2020)
Human beings are social beings, where each other needs an interaction and relationship which in this case is channeled by communication, both verbal and non verbal. One form of communication that is very important, especially that is often done in public spaces today including also in the world of music industry is a form of persuasive communication. Which in this case is a persuasive form of communication of the superstar live music event tembang pantura to attract the audience broadcast by local television Radar Cirebon. The method used in this research is qualitative descriptor method. Where researchers try to describe and analyze the data collected through literature studies, obervasi and interviews to singers in a live music event superstar tembang pantura broadcast by local television Radar Cirebon. Based on the results of literature studies, observations and interviews can be concluded: first, the persuasive communication of dangdut singer Tembang pantura in Supersetar event has not been effective enough so that the audience (audience) is less enthusiastic and lacks a good response or response to the appearance of the singer, especially when the singer performs songs that rhythmically sad. Second, persuasive communication efforts are carried out by displaying attractive dress styles, greetings using regional languages, inviting the audience to choose songs and dance together. Third, the singer's poor sound quality greatly inhibits the effectiveness of persuasive communication process performed.